From Signal to Conduct: Sequential Mediation of Green HRM in Indonesian Pulp and Paper Industry - Kusumah, Alum; Agusri, Rio; Sulistyandari, Sulistyandari; Suharto, Suharto (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2026)
Industrial sustainability in process-intensive pulp and paper operations depends heavily on systems that govern daily work. This study examines how a coordinated Green Human Resource Management (GHRM) architecture translates into Employee Green Behavior (EGB), modeling GHRM as a formative higher-order construct integrating recruitment, training, appraisal, rewards, and participation. Data from 380 employees were analyzed using PLS-SEM. The methodology includes rigorous diagnostic checks for endogeneity, predictive accuracy, and measurement invariance. The results confirm a sequential signal-to-conduct mechanism in which GHRM shapes a Green Psychological Climate that nurtures Environmental Commitment and ultimately drives EGB. A significant direct path from the GHRM bundle to behavior remains, suggesting that practices such as training scripts and appraisal dialogue nudge conduct immediately at the point of work. This mechanism is plant-wide and stable across the production, administrative roles, and tenure bands. Practically, organizations can achieve visible stewardship gains without new capital investment by sharpening training scripts, incorporating environmental evidence into performance appraisals, and maintaining low-friction participation channels. These findings clarify how environmental priorities become normal, rather than exceptional, in high-reliability industrial facilities.